Penerapan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Motivasi Dan Hasil Belajar Peserta Didik Kelas X-10 SMA Negeri Ambulu Pada Materi Pencemaran Lingkungan - Siti Nurmaida Fitria; S A Rohmah (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2023)
This study aims to determine the increase in learning motivation and learning outcomes using the Problem-Based Learning (PBL) learning model in class X-10 Ambulu State Senior High School on environmental pollution material. The research subjects totaled 36 students, consisting of 25 female students and 11 male students. This study uses a class action research method (CAR). This research was conducted in two cycles, which consisted of planning, action and observation, and reflection stages. The research data is in the form of students' learning motivation results and students' cognitive learning outcomes taken by technical description tests. The results of the questionnaire on students' learning motivation found that there were 26 students who felt happy and enthusiastic about physics lessons and 10 others who felt unenthusiastic. This shows that the learning motivation of students is good, but some others are not. The initial test cognitive learning outcomes were 59%, 74% in cycle I and increased to 88% in cycle II. This shows that the application of the PBL learning model can increase learning motivation and student learning outcomes.